Escrevendo e lendo na escola - Lima , Eliene Xavier de; Ribeiro , Marcia Cristiane; Domingos , Maria Aparecida; Auxiliadora, Maria; Okazaki , Maria Silvia Guimarães (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf